Resorcinol-, catechol- and saligenin-based bronchodilating β2-agonists as inhibitors of human cholinesterase activity - Anita Bosak; Anamarija Knežević; Ivana Gazić Smilović; Goran Šinko; Zrinka Kovarik (Taylor & Francis Group, 2017)
We investigated the influence of bronchodilating β2-agonists on the activity of human acetylcholinesterase (AChE) and usual, atypical and fluoride-resistant butyrylcholinesterase (BChE). We determined the inhibition potency of racemate and enantiomers of fenoterol as a resorcinol derivative, isoetharine and epinephrine as catechol derivatives and salbutamol and salmeterol as saligenin derivatives. All of the tested compounds reversibly inhibited cholinesterases with Ki constants ranging from 9.4 μM to 6.4 mM and had the highest inhibition potency towards usual BChE, but generally none of the cholinesterases displayed any stereoselectivity. Kinetic and docking results revealed that the inhibition potency of the studied compounds could be related to the size of the hydroxyaminoethyl chain on the benzene ring. The additional π-π interaction of salmeterol's benzene ring and Trp286 and hydrogen bond with His447 probably enhanced inhibition by salmeterol which was singled out as the most potent inhibitor of all the cholinesterases.